Comparative Evaluation of Wet and Dry Swallowing in Assessing Eustachian Tube Function in Tympanic Membrane Perforation - Kruthika, Suresh; Govindaraju, Jeevan; Shetty, Hemanth N. (International Archives of Otorhinolaryngology, 2025)
The Eustachian tube is a pressure-equalizing structure, also called the auditory tube, connecting the middle ear to the nasopharynx. Eustachian tube dysfunction is a leading cause of middle-ear infections leading to tympanic-membrane perforation. Therefore, it is necessary to assess the Eustachian tube functioning before determining the management to avoid recurrent middle-ear infections.To compare the functional assessment of the Eustachian tube by measuring pressure changes in patients with tympanic-membrane perforation, during the Toynbee test. The effectiveness of wet versus dry swallowing, ease of swallowing, and test-retest reliability for both conditions were examined.The study included 52 ears with tympanic-membrane perforations. The Toynbee test involved applying positive pressure to the ear canal while participants performed dry and wet swallowing maneuvers to measure the resulting pressure changes (in daPa). Subjective difficulty ratings were obtained using a 10-point Likert-scale for both swallowing conditions. Additionally, test-retest reliability for each swallowing condition was evaluated in 20 ears.The pressure changes observed between the open and closed phases during both swallowing conditions differed significantly. Wet swallowing exhibited a larger initial pressure change than dry swallowing (p < 0.001). Participants rated wet swallowing as significantly easier in contrast to dry swallowing. Additionally, the test-retest reliability for wet swallowing was good (intraclass correlation coefficient [ICC] = 0.737–0.876), while it was poor for dry swallowing (ICC = 0.282–0.350).Wet swallowing reliably assesses the Eustachian tube's function in tympanic-membrane perforation cases to aid in informed decision making on the possible method of tympanoplasty.
Keywords: auditory tube; pressure change; perforation; tympanic membrane; ear infection